Pengelolaan Keuangan, Transparansi, dan Pengendalian Internal terhadap Kinerja Keuangan Desa: Studi pada Pemerintah Desa Papahan Kabupaten Karanganyar - Rahmat Bayu Samudra; Yuwita Ariessa Pravasanti; LMS Kristiyanti (Jurnal Ilmiah Keuangan Akuntansi Bisnis, 2026)
Village financial performance is an important indicator in assessing the effectiveness of public financial management at the village government level. The implementation of good governance through accountable financial management, transparency, and effective internal control systems is expected to improve the quality of village financial performance. This study aims to analyze the effect of financial management, transparency, and internal control on village financial performance. This study employed a quantitative approach using a survey method. The population consisted of village officials as well as RT and RW leaders in Papahan Village, Tasikmadu District, Karanganyar Regency. A total of 90 respondents were selected using a saturated sampling technique. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with the assistance of SPSS software. The results show that financial management, transparency, and internal control have a positive and significant effect on village financial performance. Simultaneously, these variables explain 64.6% of the variation in financial performance, while the remaining 35.4% is influenced by other variables outside the research model. These findings indicate that the implementation of good governance principles plays an important role in improving accountability and effectiveness in managing public finances at the village level.